2014
DOI: 10.1155/2014/585723
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Porcine Dermal Collagen (Permacol) Implant for Abdominal Wall Reconstruction in a Pediatric Multitrauma Patient

Abstract: The presence of a contaminated surgical field in abdominal wall defects caused by trauma presents a challenge for surgeons. Both primary suture and synthetic meshes are strongly discouraged as surgical treatments in such cases. We describe the use of a porcine dermal collagen (Permacol) implant in an eight-year-old patient with multiple injuries. Three months after discharge, the child remains well with good cosmetic results. He is free of pain and has returned to full activity levels with complete wound closu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Biological prosthesis seems to have long-term durability with no incisional hernia on short and medium-term follow-up [123127] (EL 4). The three articles selected assert that Permacol was effective for the reconstruction of the abdominal wall defect in particular cases: multi-trauma, conjoined twin, and in assisting abdominal wall closure of pediatric renal transplant recipient [124, 128, 129] (EL 4).…”
Section: Resultsmentioning
confidence: 99%
“…Biological prosthesis seems to have long-term durability with no incisional hernia on short and medium-term follow-up [123127] (EL 4). The three articles selected assert that Permacol was effective for the reconstruction of the abdominal wall defect in particular cases: multi-trauma, conjoined twin, and in assisting abdominal wall closure of pediatric renal transplant recipient [124, 128, 129] (EL 4).…”
Section: Resultsmentioning
confidence: 99%
“…Mitchell et al reported no recurrences in patients treated with Permacol comparatively with 28% recurrence rate in those repaired with Gore-Tex in a case series of 37 neonates who underwent a patch repair of congenital diaphragmatic hernia [ 26 ]. Moreover, there is a case report with the application of Permacol for a traumatic abdominal wall repair in an 8-year-old boy with a favorable outcome [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biological prosthesis seems to have long term durability with no incisional hernia on short and medium term follow-up [5] , [15] , [16] , [17] , [18] . 3 articles selected in our meta-analysis assert that Permacol was effective for the reconstruction of the abdominal wall defect in particular cases: multitrauma, conjoined twin, and in assisting abdominal wall closure of pediatric renal transplant recipient [5] , [6] , [7] . Also in the treatment of giant omphalocele biologic mesh was applied as a primary abdominal fascia substitute with good results, no fascial dehiscence or infections were reported [19] , [20] , [21] , [22] , [23] , [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Research in recent years has developed biological dermal scaffolds made from a sheet of acellular matrix that can provide the desired support and reduce the occurrence of complications from non-absorbable implant (Permacol, Alloderm, Surgisis). Since 2001 Permacol™ Biological Implant has been successfully used in some pediatric and neonatal surgical cases, in particular to repair abdominal wall defects and congenital diaphragmatic hernia [4] , [5] , [6] , [7] . It is a sterile acellular sheet derived from porcine dermal collagen, indicated for reconstruction, recontouring and reformation of human soft connective tissue particularly where loss of dermis has occurred, and as a supporting tissue in surgical procedures such as abdominal wall hernias and defects.…”
Section: Introductionmentioning
confidence: 99%